The UK’s corporate killing law: Un/fit for purpose?: - Tombs, Steve (Criminology & criminal justice, 2018)
The annual total of occupational deaths in the UK is measured in the tens of thousands, yet the overwhelming majority attract no criminal justice attention. More recently, a very small number of deaths have generated attempts to prosecute companies for manslaughter. In 1996, following a series of multiple fatality ‘disasters’, the Law Commission proposed for a new law on corporate manslaughter; in 2008, the Corporate Manslaughter and Corporate Homicide Act 2007 came into force. It is with the implementation and effects of this Act that this article is concerned. It begins by setting out the dimensions of the new law before analysing the key themes that have emerged from its use to date. In conclusion, I consider whether the law has proven to be unfit for purpose—which begs the question of what that purpose might have been.